CHARACTERISTICS OF THE CAUSATIVE AGENTS OF ACUTE RESPIRATORY VIRAL INFECTIONS AND THE IMPORTANCE OF DISINFECTION MEASURES IN PREVENTING THEIR SPREAD - L. V. Rubis (Детские инфекции (Москва), 2018)
The article presents a review of the literature about the etiological structure of respiratory infections in the modern period, the role of viruses agrippinae etiology in the formation of severe diseases of the respiratory system and their stability in the environment. The purpose of the study was to explore the meaning and possibilities of improving the efficiency of sanitary and anti-epidemic measures in periods of rapid rise in the incidence of acute respiratory viral infections. It is established that at different times of the year in the formation of a rapid rise in the incidence leading role is played by rhinoviruses, RS virus and influenza virus. Epidemiological significance of rhinoviruses is their massive selection and stability in the external environment, much higher than the resistance of influenza viruses. The necessity of strengthening the disinfection measures in the autumn a rise in morbidity The necessity of strengthening the disinfection measures in the autumn a rise in incidence.